Evaluation of Immunoglobulin Y (IgY) in Canine Parvoviral Enteritis Infected Dogs - kumar, Viswanathan Naveen; Kannan, Porteen; Bharathi, Mangalanathan Vijaya; Nag, Pradeep; Maroudam, Veersami; Nagarajan, Balasubramanian; Bhaskaran, Mohana Subramanian (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Canine Parvoviral Enteritis (CPE) is one of the enzootic canine viral diseases of dogs with huge morbidity and mortality even in vaccinated population. Low success rate and unpredictable prognosis of the existing symptomatic treatment regimen demands the need of new alternative regimen for the successful CPE therapy in dogs. In the present study, a total of 60 naturally infected canine parvoviral enteritis cases were divided into routine supportive care group (n=30) and Immunoglobulin Y (IgY) added supportive care group (n=30). In the IgY added group, enteric protected IgY tablets were used along with other usual symptomatic supportive treatment. Clinical parameters and survival rate was recorded until complete recovery from CPE. It was observed that IgY added supportive care group animals had significantly higher survival rate (83.33 %), lower mean clinical score and earlier recovery from the disease.